Addressing Female Sexual Function after Cancer by Internists and Primary Care Providers. (6th February 2013) - Bober, Sharon L.; Carter, Jeanne; Falk, Sandy
ABSTRACT: Introduction.  There are now almost 14 million cancer survivors in the United States, and for the majority of survivors, the bulk of post‐cancer medical care is provided by community primary care providers (PCPs). Sexual dysfunction is one of the most common and distressing quality of life issues facing female cancer survivors yet it has become increasingly evident that women's cancer‐related sexual dysfunction often goes unaddressed, including in primary care treatment setting. Aim.  Building on a model that calls for an integrative approach to treatment, the aim is to concisely review barriers and challenges of managing cancer‐related female sexual dysfunction for PCPs and to offer specific and effective strategies that PCPs may use to treat common sexual problems in their female cancer survivors. Methods.  Literature was reviewed for relevant publications on the topic of treating cancer‐related sexual dysfunction and primary care, and interviews were conducted with experts on state‐of‐the‐art methods for treating cancer‐related sexual dysfunction. Main Outcome Measure.  Clinical evidence that demonstrates the effectiveness of simple strategies to manage cancer‐related female sexual dysfunction. Results.  Cancer‐related female sexual dysfunction does not seem to be appropriately acknowledged and addressed in primary care treatment settings. There is evidence to show that simple and effective strategies exist to ameliorate many of these problems. Conclusions.  PCPs provide the bulk of survivorship care and are therefore in a critical position to initiate assessment and treatment for female survivors with cancer‐related sexual dysfunction. Although PCPs are in need of increased support and preparation to manage this aspect of survivorship care, simple and effective strategies are available for PCPs to offer women as part of their clinical practice.Bober SL, Carter J, and Falk S. Addressing female sexual function after cancer by internists and primary care providers. J Sex Med 2013;10(suppl 1):112–119.